The choice of Zn or ZnS layer in the stacked precursors for preparation of Cu2ZnSnS4 (CZTS) thin films. (October 2020) - Olgar, M.A.; Seyhan, A.; Sarp, A.O.; Zan, R.
Abstract: Cu2 ZnSnS4 (CZTS) thin films are commonly used as an absorber layer in the thin film solar cell structure. In this study, CZTS thin films were produced by sulfurization of stacked precursor films that is prepared by deposition of Cu, Zn, SnS, ZnS films on glass substrate using sputtering method. The sequential sputter deposition was performed to obtain two distinct stacked precursors, Cu/SnS/Zn/Cu and Cu/SnS/ZnS/Cu respectively. Afterwards, annealing process was implemented at various reaction temperatures (500–575 °C) for 1 min utilizing rapid thermal processing (RTP). The EDX measurements revealed that all the prepared CZTS samples had Cu-poor and Zn-rich composition that are non-stoichiometric chemical composition. This non-stoichiometric composition is important for high efficient CZTS based solar cells. XRD measurements revealed that all patterns are dominated by diffraction planes of kesterite CZTS. The CuS, Cu2 S and SnS2 secondary phases also were detected in the XRD pattern of some CZTS films. Raman spectroscopy measurements verified formation of kesterite CZTS phase for all films and picked out CTS phase for some samples prepared using Cu/SnS/Zn/Cu precursor films. The surface microstructure of the films that were obtained through SEM displayed polycrystalline surface structure. Room temperature PL emission spectra of the films showed broad peak at around 1.37–1.38 eV, which is near to the optical band gap of kesterite CZTS structure. Electrical characterization of the samples demonstrated that B-525 CZTS thin film has more suitable electrical resistivity and carrier concentration values for CZTS based solar cell applications. Highlights: CZTS thin films were prepared by a two-stage process. Two different stacking order were employed, Cu/SnS/Zn/Cu and Cu/SnS/ZnS/Cu. Four different sulfurization temperature (500, 525, 550 and 575 °C) were used. Impact of Zn and ZnS layers in the stacked precursor films was compared. The sample reacted at 525 °C using Cu/SnS/ZnS/Cu revealed better properties.